Antifungal treatment affects the laboratory diagnosis of invasive aspergillosis. Issue 1 (2nd November 2011) - McCulloch, Elaine; Ramage, Gordon; Rajendran, Ranjith; Lappin, David F; Jones, Brian; Warn, Peter; Shrief, Raghdaa; Kirkpatrick, William R; Patterson, Thomas F; Williams, Craig
Abstract : Aims: The purpose of this study was to investigate the performance of non-invasive diagnostic tests such as galactomannan enzyme immunoassay and quantitative PCR in the early diagnosis of invasive aspergillosis (IA), and how these tests are impacted upon by the use of different classes of antifungal agents in an in-vivo model of IA. Methods: A standardised rat inhalation model of IA was used to examine the effects of an azole, posaconazole, a polyene, amphotericin B and an echinocandin caspofungin. Daily blood samples were collected for subsequent analysis using a commercially available galactomannan assay and an inhouse qPCR assay. Results: No significant differences were observed in the CE/g of Aspergillus fumigatus in the lungs of each group. qPCR was statistically more sensitive than galactomannan for both the early detection of infected controls (p=0.045) and for overall detection (p=0.018). However, antifungal treatment significantly reduced the overall sensitivity of qPCR (p=0.020); these effects were due to posaconazole and caspofungin. In the latter stages of infection (days 4 and 5) there were no significant differences in the numbers of infections detected by galactomannan and qPCR; however, the antifungal class used caused significant qualitative differences (p=0.041). Galactomannan showed improved detection in posaconazole-treated animals. Conclusions: Previous exposure to antifungal therapy must be considered when interpreting either qPCR or galactomannan-based IA diagnostics as this study has shown that individual classes of antifungal agents impact upon the dynamics of antigen and DNA release into the circulation.